Location, location, location: considerations when using lightweight drones in challenging environments - Duffy, James P.; Cunliffe, Andrew M.; DeBell, Leon; Sandbrook, Chris; Wich, Serge A.; Shutler, Jamie D.; Myers‐Smith, Isla H.; Varela, Miguel R.; Anderson, Karen; Pettorelli, Nathalie; Horning, Ned (Remote sensing in ecology and conservation, 2018)
Lightweight drones have emerged recently as a remote sensing survey tool of choice for ecologists, conservation practitioners and environmental scientists. In published work, there are plentiful details on the parameters and settings used for successful data capture, but in contrast there is a dearth of information describing the operational complexity of drone deployment. Information about the practices of flying in the field, whilst currently lacking, would be useful for others embarking on new drone‐based investigations. As a group of drone‐piloting scientists, we have operated lightweight drones for research in over 25 projects, in over 10 countries, and in polar, desert, coastal and tropical ecosystems, with many hundreds of hours of flying experience between us. The purpose of this paper was to document the lesser‐reported methodological pitfalls of drone deployments so that other scientists can understand the spectrum of considerations that need to be accounted for prior to, and during drone survey flights. Herein, we describe the most common challenges encountered, alongside mitigation and remediation actions that increase the chances of safe and successful data capture. Challenges are grouped into the following categories: (i) pre‐flight planning, (ii) flight operations, (iii) weather, (iv) redundancy, (v) data quality, (vi) batteries. We also discuss the importance of scientists undertaking ethical assessment of their drone practices, to identify and mitigate potential conflicts associated with drone use in particular areas. By sharing our experience, our intention is that the paper will assist those embarking on new drone deployments, increasing the efficacy of acquiring high‐quality data from this new proximal aerial viewpoint. Despite the increasing deployment of drones for environmental and ecological research purposes, there is a lack of methodological information in the literature. We provide structured presentation of the challenges faced in the field, and ways to prevent or overcome them to maximize successful data capture.